2014
DOI: 10.1007/s00402-014-2126-1
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of intraoperative navigation on glenoid component positioning during total shoulder arthroplasty

Abstract: Level II-meta-analysis of non-homogenous controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 29 publications
0
29
0
5
Order By: Relevance
“…A comprehensive review of the literature confirmed its superior accuracy to the conventional method regarding the positioning of the glenoid component. 14 The navigation has benefits for both ATSA 1,10,16 and RTSA, 12,15,16,21 especially when the anatomy is distorted by fractures, revisions, wear, or dysplasia of the glenoid. 9,10 The contraindications to navigation are the same for shoulder arthroplasties, such as active or latent infection and generally poor health.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of the literature confirmed its superior accuracy to the conventional method regarding the positioning of the glenoid component. 14 The navigation has benefits for both ATSA 1,10,16 and RTSA, 12,15,16,21 especially when the anatomy is distorted by fractures, revisions, wear, or dysplasia of the glenoid. 9,10 The contraindications to navigation are the same for shoulder arthroplasties, such as active or latent infection and generally poor health.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the need for clear en-face access to the joint surfaces requires humeral dislocation, which has been linked to intraoperative nerve injury [12][13][14]. Furthermore, traditional surgical techniques have been shown to be prone to outliers in implantation accuracy that are associated with poor TSA outcomes [15][16][17][18][19][20]. These complications are particularly problematic in younger patients who have greater functional expectations and who necessitate longer implant survival [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, intraoperative real- time 3D image intensifier based reconstructions combined with navigation is known to ensure accurate implant positioning and reducing complications using intraoperatively acquired images [16, 17]. Thus, navigated implantation of shoulder arthroplasty has an increasing role [4, 11, 18, 19] and might improve positioning of the glenoid component [4, 18, 20, 21]. Although a few cadaver studies suggest a benefit of intraoperative 3D imaging combined with navigation in rTSA [22, 23], clinical studies are still rare.…”
Section: Introductionmentioning
confidence: 99%